Sacred atmospheres. A baroque church in a market as a case study: atmosphere - De Stefano, Elisabetta (Scenari, 2021)
Although architecture has often granted a key role to the geometry-based Cartesian space and to the visual paradigm, the aesthetics of atmosphere – understood as an enquiry into the relationship between environmental expressive qualities and subjectively registered conditions – is able to provide further theoretical perspectives. The paper highlights that the aesthetics of atmospheres, taking into account all the senses, should be considered as a valid interpretative tool to integrate the traditional point of view of the history of architecture. To demonstrate this, the paper will focus on a case study: the baroque church of Immacolata Concezione al Capo, set in one of the historical markets of Palermo.